2018
DOI: 10.21273/hortsci12455-17
|View full text |Cite
|
Sign up to set email alerts
|

Propagation Daily Light Integral and Root-Zone Temperature Influence Rooting of Single-internode Pennisetum ×advena Culm Cuttings

Abstract: Crown division, tissue culture, and culm cuttings are methods for propagating purple fountain grass [Pennisetum ×advena Wipff and Veldkamp (formerly known as Pennisetum setaceum Forsk. Chiov. ‘Rubrum’)]. However, propagation by culm cuttings is becoming an economically attractive method for quick liner production. Our objective was to quantify the impact of propagation daily light integral (PDLI) and root-zone temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
1
6
0
1
Order By: Relevance
“…1C and 2C). This corresponds with the findings of others who have reported a general increase in biomass production of transplants with higher (but not saturating) PPFDs (Currey et al, 2012;Hern andez and Kubota, 2014;Isutsa et al, 1994;Loach and Gay, 1979;Lopez and Runkle, 2008;Owen and Lopez, 2018;Pramuk and Runkle, 2005;Tombesi et al, 2015;Torres and Lopez, 2011). Numerous studies have shown that for seedlings, and to an extent for unrooted cuttings, higher DLIs typically provided with higher PPFDs, promote root initiation and formation, and shoot and root growth (Faust et al, 2017;Randall and Lopez, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…1C and 2C). This corresponds with the findings of others who have reported a general increase in biomass production of transplants with higher (but not saturating) PPFDs (Currey et al, 2012;Hern andez and Kubota, 2014;Isutsa et al, 1994;Loach and Gay, 1979;Lopez and Runkle, 2008;Owen and Lopez, 2018;Pramuk and Runkle, 2005;Tombesi et al, 2015;Torres and Lopez, 2011). Numerous studies have shown that for seedlings, and to an extent for unrooted cuttings, higher DLIs typically provided with higher PPFDs, promote root initiation and formation, and shoot and root growth (Faust et al, 2017;Randall and Lopez, 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Wilkerson et al (2005) suggested that the poinsettia rooting percentage is greatest when root zones are 27 to 29°C, and declines at higher or lower temperatures. Owen and Lopez (2018) showed that both root-zone temperature and light impact rooting percentage of purple fountain grass (Pennisetum •advena). At a low DLI (4-10 mol • m -2 • d -1 ), increasing temperature increased rooting percentage, whereas at a higher DLI (8-16 mol • m -2 • d -1 ), rooting percentage increased up to an optimum temperature of 23°C and then declined (Owen and Lopez, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Owen and Lopez (2018) showed that both root-zone temperature and light impact rooting percentage of purple fountain grass (Pennisetum •advena). At a low DLI (4-10 mol • m -2 • d -1 ), increasing temperature increased rooting percentage, whereas at a higher DLI (8-16 mol • m -2 • d -1 ), rooting percentage increased up to an optimum temperature of 23°C and then declined (Owen and Lopez, 2018). Greater root-zone temperatures in submist and combination systems might, in part, account for their increased quality of root systems relative to overhead mist, but lower aerial temperatures in combination systems might, in turn, account for the increased rooting percentage in combination systems relative to submist alone.…”
Section: Resultsmentioning
confidence: 99%
“…Enfield et al (2003) reported that garden phlox (Phlox paniculata) cuttings required at least 3.5 mol • m -2 • d -1 for rapid, uniform rooting. Owen and Lopez (2018) propagated fountain grass (Pennisetum •advena) culm cuttings at DLIs from 4 to 16 mol • m -2 • d -1 and reported that the most efficient rooting occurred at 8-10 mol • m -2 • d -1 , whereas the highest DLI (16 mol • m -2 • d -1 ) had lower culm and root density. Currey et al (2012) examined the effect of DLI after callus formation on the cuttings of nine annual species.…”
Section: Discussionmentioning
confidence: 99%